Formulation and Evaluation of Controlled Release Microspheres of Acyclovir for Antiviral Therapy - Shashidhar, Dr. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: Controlled drug delivery system (CDDS) provides the continuous oral drug delivery at predictable and reproducible kinetics for a predetermined period throughout the course of Gastro intestinal transit and emerges various routes of administration to achieve oral controlled drug delivery. Aim of this study was to formulate and evaluate controlled release microspheres of Antiviral drug, Acyclovir. Polymethacrylates (Eudragits) used as release retardant polymer material. Material & Methods: Microspheres prepared by non-aqueous solvent evaporation method using alcohol/light liquid paraffin. Magnesium stearate act as a droplet stabilizer and n-hexane is to harden the microspheres. The microspheres evaluated for their compatibility study Fourier transform infra-red(FT-IR), differential scanning calorimeter(DSC), flow & micromeritics properties, particle size, drug content, entrapment efficiency, In vitro dissolution study in both 1.2 and 6.8 pH buffer, Scanning Electron Microscope(SEM) and accelerated stability study. Results & Discussion: The prepared microspheres were free flowing and spherical shape. The actual drug content in microspheres showed entrapment and release controlled till 12h the rate of drug release was found to decrease with increasing sphere size. The compatibility studies showed no interactions in formulations. Scanning electron microscope study of microspheres were Spherical and porous in nature. The best fit release kinetics achieved was Hixon-crowell plot. Conclusion: The formulation and evaluation of Controlled Release Acyclovir microspheres is influenced by drug to polymer ratio and particle size and was found to be dissolution controlled. The formulation enhanced bioavailability upto 24hrs.